AIPISteg: An active IP identification based steganographic method - Abdullaziz, O.I.; Goh, V.T.; Ling, H.C.; Wong, K.S. (Elsevier, 2016)
IP identification (IPID) is an IP header field which is designed to identify a packet in a communication session. The main purpose of IPID is to recover from IP fragmentation. To the best of our knowledge, most existing IPID based information hiding methods assume that the IPID number is a pseudo random number, which is found to be false. In this paper, we propose a steganographic method by exploiting the IPID field while considering the information from the user data field. First, we analyze the IPID distribution of various operating systems. Subsequently, we put forward a simple data embedding method, which is then refined to mimic the ordinary IPID traffic. Experiments are carried out and the results empirically prove that the proposed method is of high undetectability as compared to the existing IPID based steganographic methods.